2011
DOI: 10.1007/s10143-011-0322-9
|View full text |Cite
|
Sign up to set email alerts
|

Endoscope-assisted microsurgical resection of skull base meningiomas

Abstract: This study aims to determine the value of endoscope assistance in the microsurgical resection of skull base meningiomas. Fourty-six patients harboring a skull base meningioma underwent an endoscope-assisted microsurgical resection. In 30 patients (65%), tumor parts which could not be visualized under the microscope were detected with the endoscope. In 26 patients (56%), these tumor remnants were removed under endoscopic view. Gross total resection was achieved in 35 patients (76%) and near-total resection in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 38 publications
3
42
1
Order By: Relevance
“…CSF leaks, however, were higher in patients recovering from endoscopic surgery [68]. Interestingly, one study reviewing skull-based meningiomas notes that the use of the endoscope allowed further visualization of tumor that a microscope could not see in 65% of patients [19]. A literature review comparing only open transcranial versus transphenoidal craniopharyngiomas showed that the endoscopic study had greater rate of total resection and improved postoperative visual outcome [69].…”
Section: Postoperative Carementioning
confidence: 97%
See 1 more Smart Citation
“…CSF leaks, however, were higher in patients recovering from endoscopic surgery [68]. Interestingly, one study reviewing skull-based meningiomas notes that the use of the endoscope allowed further visualization of tumor that a microscope could not see in 65% of patients [19]. A literature review comparing only open transcranial versus transphenoidal craniopharyngiomas showed that the endoscopic study had greater rate of total resection and improved postoperative visual outcome [69].…”
Section: Postoperative Carementioning
confidence: 97%
“…Treatment options include monitoring small slow-growing lesions, radiation or surgical resection. The most common surgical complication is cranial nerve palsies [19].…”
Section: Tumor Differential Diagnosis and Treatmentmentioning
confidence: 99%
“…When using small craniotomies, which allow only a nearly coaxial vision, the endoscope is mandatory to inspect any corner of the surgical field [ 19 ].…”
Section: Posterior Fossa Skull Base Meningiomasmentioning
confidence: 99%
“…2,3,26 Endoscopic techniques for cer-ebellopontine angle (CPA) surgery have been well studied and applied to tumor resection, vascular decompression, and aneurysm surgery. 5,8,10,[17][18][19]22,23,28,32,[34][35][36]39,40,42 The advantages have been emphasized in the context of minimally invasive craniotomies, 4,13,15,31 increasing visualization of hidden anatomy, and inspecting around corners. 6,7,14,23,33,43, abbreviations CPA = cerebellopontine angle; EVTR = endoscopically verified total resection.…”
mentioning
confidence: 99%